The Impacts of Entrepreneurial Orientation Dimensions to the Success of Malaysian Smes - Mohd Nordin, Noorain; Mohamed, Munirah; Azrin Ariffin, Nurul; Norhisham, Norshiba; Zaitun Saddam, Siti; Kalsum Hassian, Ummi; Hasan, Zuhairah (International Journal of Engineering and Technology, 2018)
Firms are always seeking for new opportunities to achieve higher performance, especially Small and Medium Enterprises (SMEs), which some has been evaluated by SME Corporation. However, none of SMEs in Malaysia achieves the highest performance according to their score measurement. The aims of study were to determine the relationship between the EO and firm performance and determine the significant predictor variable of firm performance among SMEs. There are five dimensions of EO namely innovation, risk taking, market proactiveness, autonomy and competitive aggressiveness used to analyse which dimension are the most important using a statistical analyses such as correlation and multiple regression analysis. Based on the findings, SMEs should focus more on risk taking, market proactiveness and innovativeness in order to increase the performance of their firms in the challenging business market. Â Â